A covalent organic framework nanotube, a polymer electrolyte and a preparation method thereof
Patent Information
- Application Number
- CN202311010854.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-08-11
AI Technical Summary
然而,常规固态聚合物电解质仍然面临着离子电导率低、钠离子迁移数小、循环稳定性差等问题
[0041](1)本发明所合成的自组装中空管状共价有机框架,即共价有机框架纳米管,呈现出由片状结构自组装而成的高长径比的纳米管状结构,实现了高性能电解质填料的合成,拓宽了全固态电解质的优化策略。
Smart Images

Figure CN117186419B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion batteries, specifically to a covalent organic framework nanotube, a polymer electrolyte, and a method for preparing the same. Background Technology
[0002] The development of energy storage devices is one of the most effective ways to solve the current energy shortage and low utilization problems. Currently, lithium batteries, as typical rechargeable batteries, have received extensive research. However, the scarcity of lithium resources and their high cost severely hinder their development. Compared to lithium batteries, sodium-ion batteries, composed of sodium with similar physicochemical properties to lithium, have the advantages of wide resource distribution and low cost. Furthermore, they can follow some of the industrial routes used in lithium-ion batteries to achieve rapid industrialization. In addition, sodium-ion batteries possess high safety and adaptability, as well as excellent high and low temperature performance, enabling wider and deeper applications in certain fields, especially in large-scale energy storage.
[0003] Electrolytes, as one of the most crucial components in constructing sodium-ion batteries, can be categorized into liquid electrolytes and solid electrolytes based on their state. Currently, sodium-ion batteries primarily use organic ether-based liquid electrolytes. However, during battery use, flammable and volatile organic liquid electrolytes are prone to thermal runaway, leading to serious safety accidents. Furthermore, organic electrolytes have a narrow electrochemical window, are unstable with metallic sodium, and are difficult to match with high-voltage positive and metallic sodium negative electrodes, severely limiting the improvement of sodium-ion battery energy density.
[0004] Replacing liquid electrolytes with solid polymer electrolytes to construct solvent-free all-solid-state sodium-ion batteries not only solves the aforementioned safety issues, but also allows for stable contact interfaces and a wider range of anode material selection, thus enabling the optimization of sodium-ion batteries with high safety and high energy density. However, conventional solid polymer electrolytes still face problems such as low ionic conductivity, low sodium ion transport number, and poor cycle stability. Incorporating functional materials as fillers into solid polymer electrolytes has been extensively studied as a direct and effective method, but significant bottlenecks remain in improving overall performance. Therefore, developing high-performance functional fillers and high-performance all-solid-state electrolytes are major technical challenges for realizing the commercial application of sodium-ion batteries. Summary of the Invention
[0005] The purpose of this invention is to provide a self-assembled hollow tubular covalent organic framework, namely covalent organic framework nanotubes, and to use these covalent organic framework nanotubes as functional fillers to prepare polymer-based solid electrolytes by combining them with polymers. The synthesis method of the covalent organic framework nanotubes provided by this invention is specific and efficient. The polymer-based solid electrolytes modified with these nanotubes as functional fillers have high ionic conductivity, high sodium ion transference number, excellent mechanical properties, and good interfacial stability with the sodium metal anode.
[0006] To achieve the above objectives, the present invention first provides a method for preparing covalent organic framework nanotubes, the method comprising the following steps:
[0007] (1) Preparation of electrospun base film: Dissolve polar polymer in polar organic solvent to prepare electrospun precursor, and obtain electrospun base film by electrospun the obtained electrospun precursor.
[0008] (2) Preparation of covalent organic framework nanotubes: Boric acid monomer, ligand and electrospun base film are mixed into an organic solvent to form a mixed solution. After freezing and degassing, the covalent organic framework is induced to grow in situ through solvothermal reaction and undergo structural rearrangement. The covalent organic framework material is obtained by washing with acetone or acetonitrile. The washed material is activated in acetone for 12h to 36h and then vacuum dried to obtain covalent organic framework nanotubes.
[0009] In one embodiment of the present invention, in step (1), the polar polymer may be any polar polymer known in the art, including any one of polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyimide (PI), and polyurethane (PU), preferably polyacrylonitrile (PAN).
[0010] In one embodiment of the present invention, in step (1), the polar organic solvent may be any polar organic solvent known in the art, including any one of N,N-dimethylformamide DMF, dimethyl sulfoxide DMSO, and sulfolane, preferably N,N-dimethylformamide DMF.
[0011] In one embodiment of the present invention, in step (1), the mass-to-volume ratio of the polar polymer to the polar organic solvent is 1 to 3.75 mg / mL, preferably 2 mg / mL.
[0012] In one embodiment of the present invention, in step (1), the high voltage during electrospinning is 14 to 18 KV and the low voltage is -3 to 0 KV. Preferably, the high voltage is 16 KV and the low voltage is -2 KV.
[0013] In one embodiment of the present invention, in step (1), the spinning distance during electrospinning is 15-25 cm, preferably 20 cm, and the rotation speed of the receiver is 80-150 rpm, preferably 100 rpm.
[0014] In one embodiment of the present invention, in step (1), the ambient humidity during electrospinning is 50-80%, preferably 75%, and the ambient temperature is 25-35°C, preferably 30°C.
[0015] In one embodiment of the present invention, in step (2), the boric acid monomer includes any one of 1,4-phenyldiboronic acid (BDBA), biphenyl diboronic acid (BPDA), 1,3,5-phenyltriboronic acid (BTBA), and 1,3,5-phenyl ester (4-phenylboronic acid) (BTPA), preferably 1,4-phenyldiboronic acid (BDBA).
[0016] In one embodiment of the present invention, in step (2), the ligand comprises 1,4-phenyldiboronic acid (BDBA) and / or 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP), preferably 1,4-phenyldiboronic acid (BDBA).
[0017] In one embodiment of the present invention, in step (2), the organic solvent is a mixed solution of m-trimethylbenzene and 1,4-dioxane, with a volume ratio of (0.5-1.5):(1.5-0.5), preferably (0.8-1.2):(1.2-0.8), and more preferably 1:1.
[0018] In one embodiment of the present invention, in step (2), the number of times of freezing and degassing is 1 to 4, preferably 3 times.
[0019] In one embodiment of the present invention, in step (2), the temperature of the solvothermal reaction is 100-150°C, preferably 120°C, and the reaction time is 24-96h, preferably 72h.
[0020] In one embodiment of the present invention, in step (2), anhydrous acetone or anhydrous acetonitrile is used for washing 1 to 4 times, and the washed material is placed in acetone for 12 to 36 hours, preferably 24 hours, for activation.
[0021] In one embodiment of the present invention, in step (2), the vacuum drying time is 12 to 36 hours, preferably 24 hours, and the vacuum drying temperature is 100 to 150°C, preferably 120°C.
[0022] The present invention also provides a covalent organic framework nanotube prepared according to the above method.
[0023] In one embodiment of the present invention, the molecular structure of the covalent organic framework nanotube includes any one of the following structural formulas:
[0024]
[0025] The present invention also provides a polymer-based electrolyte reinforced by covalent organic framework nanotubes, wherein the polymer electrolyte comprises the above-mentioned covalent organic framework nanotubes, a polymer matrix, and a sodium salt.
[0026] In one embodiment of the present invention, the polymer matrix comprises polyethylene oxide (PEO) or polyphenylene oxide (PPO), preferably polyethylene oxide (PEO).
[0027] In one embodiment of the present invention, the sodium salt is selected from sodium salts known in the art, preferably sodium salts adapted to sodium-ion batteries, and the sodium salt includes at least one of NaClO4, NaPF6, NaFSI, NaTFSI, and NaBF4, preferably NaTFSI.
[0028] In one embodiment of the present invention, the mass ratio of the polymer matrix to the sodium salt is 8 to 20:1, preferably 16:1; the mass ratio of the covalent organic framework nanotube to the polymer matrix is 1 to 10:100.
[0029] This invention also provides a method for preparing a polymer-based electrolyte reinforced with covalent organic framework nanotubes, comprising the following steps:
[0030] (1) Preparation of polymer electrolyte membrane: Covalent organic framework nanotubes are dispersed in an organic solvent and ultrasonically treated to obtain a covalent organic framework nanotube dispersion. Then, a polymer matrix and sodium salt are added to the dispersion to prepare a homogeneous solution. Finally, the solution is cast into a mold to form a membrane, thus obtaining a polymer electrolyte membrane.
[0031] (2) Vacuum hot pressing and drying treatment: The polymer electrolyte membrane prepared in step (1) is placed in the battery mold and vacuum hot pressing treatment is performed to obtain the polymer electrolyte.
[0032] In one embodiment of the present invention, the concentration of nanotubes in the covalent organic framework nanotube dispersion is 1-10%, and the organic solvent includes at least one of anhydrous acetonitrile, tetrahydrofuran, and N-methylpyrrolidone.
[0033] In one embodiment of the present invention, the mass fraction of the polymer matrix in the homogeneous solution is 2-10%, and the mass ratio of the polymer matrix to the sodium salt is 8-20:1.
[0034] In one embodiment of the present invention, in step (1), the frequency of ultrasonic treatment is 80-120Hz, the power is 30-50W, and the time is 0.5-2h, preferably the frequency is 100Hz, the power is 40W, and the time is 1h.
[0035] In one embodiment of the present invention, in step (2), the load pressure of the battery mold is 5 to 20 N, preferably 10 N.
[0036] In one embodiment of the present invention, in step (2), the temperature during vacuum hot pressing is 50 to 80°C, preferably 60°C.
[0037] The present invention also provides an application of the above-mentioned polymer electrolyte in an energy storage battery.
[0038] In one embodiment of the present invention, the energy storage battery is selected from sodium-ion batteries, and more preferably, the sodium-ion battery is selected from all-solid-state sodium-ion batteries.
[0039] In one embodiment of the present invention, the energy storage battery includes a positive electrode, a negative electrode, and the aforementioned polymer-based composite solid electrolyte. In this invention, there is no specific limitation on the positive and negative electrodes of the energy storage battery; known positive and negative electrode materials in this technical field can be used. Exemplarily, the positive electrode includes at least one of sodium vanadium phosphate, sodium nickel iron manganese oxide, Prussian blue, sodium ion fluorophosphate, sodium iron sulfate, and sodium vanadium fluorophosphate. Exemplarily, the negative electrode contains at least one of metallic sodium, molybdenum disulfide, hard carbon, sodium titanium oxide, nickel cobalt oxide, antimony oxide, and antimony-carbon composite materials.
[0040] The beneficial effects of this invention are:
[0041] (1) The self-assembled hollow tubular covalent organic framework synthesized in this invention, namely covalent organic framework nanotubes, exhibits a high aspect ratio nanotube structure formed by the self-assembly of sheet-like structures, realizing the synthesis of high-performance electrolyte fillers and broadening the optimization strategy for all-solid electrolytes.
[0042] (2) The polymer electrolyte prepared by the present invention using covalent organic framework nanotubes as fillers has the characteristics of high ionic conductivity, high sodium ion transference number, electrochemical stability and excellent mechanical properties, which meet the practical application requirements of all-solid-state sodium-ion batteries.
[0043] (3) The electrolyte of the present invention can utilize the boron structure rich in covalent organic framework nanotubes as Lewis acid sites to capture anions, which can effectively increase the sodium ion transfer number while promoting sodium salt dissociation and reduce the concentration polarization caused by charge transfer inside the electrolyte, thereby stabilizing the sodium deposition and stripping process at the negative electrode / electrolyte interface; in addition, the high aspect ratio nanotube structure greatly promotes the dispersion of covalent organic framework nanotube filler in the polymer matrix, destroys the crystalline part of the polymer matrix, significantly reduces its crystallinity, thereby creating more efficient ion transport regions, which significantly improves the ionic conductivity of the polymer electrolyte; in addition, covalent organic framework nanotubes also construct a fast and highly selective sodium ion transport channel, enabling the all-solid-state sodium ion battery to exhibit good cycle stability and rate performance.
[0044] (4) The electrolyte of the present invention has a unique composition and structure, which can simultaneously enhance the stability of the positive electrode / electrolyte interface and the negative electrode / electrolyte interface. The assembled all-solid-state sodium-ion battery has good rate performance and cycle stability. In addition, the main material of the polymer-based composite solid electrolyte (mainly composed of polymer matrix and covalent organic framework nanotubes) is inexpensive and low-cost. Moreover, the preparation process of the polymer electrolyte of the present invention is simple, which can realize the fast charge and discharge and long cycle life of the all-solid-state sodium-ion battery.
[0045] (5) The polymer electrolyte prepared by this invention has an ionic conductivity of 5.52 × 10⁻⁶ at 60 °C. -4 S cm -1 The electrochemical window can reach 6.36V vs. Na + / Na, the sodium ion transference number can reach 0.68.
[0046] (6) The all-solid-state sodium-ion battery prepared with the polymer electrolyte of the present invention has a high specific capacity, up to 116.4 mAh g. -1 The coulombic efficiency is as high as 98.3%, and the capacity retention rate is 98.9% after 20 charge-discharge cycles, indicating that the prepared sodium-ion battery has good cycle stability. Attached Figure Description
[0047] Figure 1 This is a scanning electron microscope image of S-COF in Example 1;
[0048] Figure 2 This is a transmission electron microscope image of S-COF in Example 1;
[0049] Figure 3 The results show the test results of the ionic conductivity of the polymer electrolyte in Example 2;
[0050] Figure 4The results are the electrochemical window test results of the polymer electrolyte in Example 2;
[0051] Figure 5 The charge-discharge curves of the all-solid-state sodium-ion battery in Example 5 are shown.
[0052] Figure 6 The graph shows the cycle performance of the all-solid-state sodium-ion battery in Example 5.
[0053] Figure 7 The image shows a scanning electron microscope image of COF-1 synthesized in Comparative Example 1.
[0054] Figure 8 This is a scanning electron microscope image of S-COF in Comparative Example 2;
[0055] Figure 9 The image shows a scanning electron microscope image of S-COF in Comparative Example 3.
[0056] Figure 10 The image shows a scanning electron microscope image of S-COF in Comparative Example 4.
[0057] Figure 11 This is a scanning electron microscope image of S-COF in Comparative Example 5. Detailed Implementation
[0058] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0059] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.
[0060] Electrical performance testing of polymer electrolytes
[0061] 1. Ionic conductivity of polymer-based composite solid electrolytes with high ion transport efficiency:
[0062] The prepared polymer electrolyte was sandwiched between two stainless steel sheets and assembled in a 2032 battery casing. Electrochemical impedance spectroscopy was performed using an electrochemical workstation. The ionic conductivity of the electrolyte was calculated using the following formula:
[0063] σ=L / (S*R b )
[0064] Where L is the thickness of the polymer electrolyte, S is the area of the stainless steel sheet facing each other, and R... b The measured electrolyte bulk impedance.
[0065] 2. Electrochemical window of polymer electrolytes:
[0066] The polymer electrolyte was sandwiched between a stainless steel sheet and a sodium sheet and assembled in a 2032 battery case. The electrochemical window was measured by linear voltammetry using an electrochemical workstation. The test conditions were: initial potential of 1V, maximum potential of 7V, and scan rate of 0.5mV / s.
[0067] 3. Na in polymer electrolytes + Number of migrations (t) Na + ):
[0068] A Na / electrolyte / Na symmetric cell was assembled in a 2032 battery case by sandwiching a polymer electrolyte between two sodium plates. The sodium ion transport number was measured using AC impedance spectroscopy and a potentiostatic chronoamperometry method, with a polarization voltage of 10 mV. The sodium ion transport number can be calculated using the following formula:
[0069]
[0070] Where I0 and I S The current values before and after polarization are R0 and R, respectively. S The values are the interface impedances obtained before and after polarization, respectively, and ΔV is the applied polarization voltage.
[0071] Example 1
[0072] A method for preparing covalent organic framework nanotubes includes the following steps:
[0073] (1) Preparation of electrospun matrix PFM: 1g of polyacrylonitrile (PAN) was dissolved in 5mL of N,N-dimethylformamide (DMF) to prepare a viscous spinning solution. The spinning solution was then transferred into a spinning syringe. The distance between the needle and the receiver was set to 20cm, the receiver rotation speed was set to 100rpm, the injection speed was set to 0.09cm / min, the high voltage was set to 16KV, and the low voltage was set to -2KV. After spinning was completed, the spun membrane was transferred into a vacuum drying oven and vacuum dried at 100℃ for 12h to obtain the electrospun matrix PFM.
[0074] (2) Preparation of covalent organic framework nanotubes S-COF:
[0075] In a glove box atmosphere (Ar, water <0.01ppm, oxygen <0.01ppm), 0.25g of 1,4-phenylenediboric acid (BDBA) and 10mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were prepared into a suspension. 0.02g of the electrospun base membrane PFM obtained in step (1) was added to the suspension, and the mixture was sealed in a Schlenk flask. The resulting suspension was then rapidly frozen at 77K (LN2 bath) and evacuated. The mixture was then thawed by ultrasonic treatment, and this process was repeated three times to completely remove residual air. The mixture was then placed at 120°C for 72h to obtain a covalent organic framework. After washing three times with acetone (treated with molecular sieves), the mixture was activated in acetone for 24 hours and then dried in a vacuum oven at 120°C for 12h to obtain covalent organic framework nanotubes (S-COF).
[0076] The microstructure and structure of covalent organic framework nanotubes (S-COF) were observed using scanning electron microscopy (SEM), and the results are as follows: Figure 1 As shown, Figure 1 The covalent organic framework nanotubes S-COF synthesized using the above synthesis method exhibit a high aspect ratio nanotube structure formed by the self-assembly of sheet-like structures.
[0077] The fine structure of the covalent organic framework nanotube S-COF was observed using transmission electron microscopy (TEM), and the results are as follows: Figure 2 As shown, the covalent organic framework nanotubes S-COF synthesized using the above synthesis method exhibit a hollow nanotube structure.
[0078] Example 2
[0079] A method for preparing a polymer-based electrolyte reinforced with covalent organic framework nanotubes includes the following steps:
[0080] (1) Preparation of polymer electrolyte membrane ex-HSPE: Covalent organic framework nanotubes were added to 25 mL of anhydrous acetonitrile and ultrasonically treated (frequency 100 Hz, power 40 W, time 1 h) to form a homogeneous dispersion. 5 mL of the dispersion was taken and 1 g of polyethylene oxide (PEO), 0.4303 g of sodium salt (NaFTSI) and 15 mL of anhydrous acetonitrile were added to prepare a homogeneous solution. After stirring for 6 h, the solution was cast into a mold using the solution casting method. After the acetonitrile evaporated, the membrane was formed naturally to obtain the polymer electrolyte membrane ex-HSPE, which was then stored in an inert gas.
[0081] (2) Preparation of polymer solid electrolyte HSPE:
[0082] In a glove box, the polymer solid electrolyte membrane ex-HSPE prepared in step (2) is placed in a button-type polytetrafluoroethylene mold, and after applying a load of 10N, it is moved into a vacuum drying oven and hot-pressed at 60°C for 12 hours to finally obtain the polymer solid electrolyte HSPE.
[0083] In step (1), the preparation method of covalent organic framework nanotubes is the same as that in Example 1.
[0084] The test results for the ionic conductivity and electrochemical window of the polymer electrolyte HSPE are as follows: Figure 3 and 4 As shown, the polymer electrolyte has an ionic conductivity of 5.52 × 10⁻⁶ at 60 °C. -4 S cm -1 The electrochemical window is 6.36 V vs. Na. + / Na, the sodium ion transference number is 0.68.
[0085] Example 3
[0086] The difference between Example 3 and Example 2 lies in the preparation method of the covalent organic framework nanotubes S-COF. The preparation method of the covalent organic framework nanotubes S-COF includes the following steps:
[0087] (1) The preparation method of electrospun base film PFM is the same as that in Example 1.
[0088] (2) In a glove box atmosphere (Ar, water <0.01ppm, oxygen <0.01ppm), 0.25g of 1,4-phenylenediboric acid (BDBA) and 10mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were prepared into a suspension. 0.05g of the electrospun base membrane PFM obtained in step (1) was added to the suspension and sealed in a Schlenk bottle. The resulting suspension was then rapidly frozen at 77K (LN2 bath) and evacuated. The mixture was then thawed by ultrasonic treatment. The above steps were repeated three times to completely remove residual air. The mixture was then placed at 120℃ for 72h to obtain a covalent organic framework. After washing three times with acetone (treated with molecular sieves), the mixture was activated by acetone for 24h and then dried in a vacuum oven at 120℃ for 12h to obtain covalent organic framework nanotubes S-COF.
[0089] The polymer electrolyte in Example 3 was tested and found to have an ionic conductivity of 4.29 × 10⁻⁶ at 60°C. -4 S cm -1 The electrochemical window of the polymer electrolyte is 5.48 V vs. Na. + / Na, the sodium ion transference number of the polymer electrolyte is 0.56.
[0090] Example 4
[0091] The difference between Example 4 and Example 2 lies in the amount of covalent organic framework nanotubes (S-COF) added. The preparation method of the polymer-based electrolyte reinforced with covalent organic framework nanotubes includes the following steps:
[0092] (1) Preparation of polymer electrolyte membrane ex-HSPE: Covalent organic framework nanotubes were added to 25 mL of anhydrous acetonitrile and ultrasonically treated (frequency 100 Hz, power 40 W, time 1 h) to form a homogeneous dispersion. 1 mL of the dispersion was then taken and 1 g of polyethylene oxide (PEO), 0.4303 g of sodium salt (NaFTSI) and 19 mL of anhydrous acetonitrile were added to prepare a homogeneous solution. After stirring for 6 h, the solution was cast into a mold using the solution casting method. After the acetonitrile evaporated, the membrane was formed naturally to obtain the polymer electrolyte membrane ex-HSPE, which was then stored in an inert gas.
[0093] (2) Preparation of polymer electrolyte HSPE: In a glove box, the polymer electrolyte membrane ex-HSPE prepared in step (1) is placed in a button-type polytetrafluoroethylene mold, and after applying a load of 10N, it is moved into a vacuum drying oven and hot-pressed at 60℃ for 12h to finally obtain polymer electrolyte HSPE.
[0094] The polymer electrolyte of Example 4 was tested and found to have an ionic conductivity of 4.67 × 10⁻⁶ at 60°C. -4 S cm -1 The electrochemical window of the polymer electrolyte is 5.53 V vs. Na. + / Na, the sodium ion transference number of the polymer electrolyte is 0.61.
[0095] Example 5
[0096] A fully solid-state sodium-ion battery is prepared as follows:
[0097] (1) Preparation of positive electrode sheet: Na3V2(PO4)3 positive electrode active material powder, conductive agent Super P and binder PVDF are uniformly mixed in a mass ratio of 80:10:10. N-methylpyrrolidone NMP solution is added (the mass ratio of the added amount to the positive electrode active material powder is 2:1). The mixture is stirred and ultrasonically prepared in a dry environment at room temperature to form a uniform slurry. The slurry is then coated on a dry and flat aluminum foil, transferred to a vacuum drying oven for drying, and finally cut into round sheets with a diameter of 12 mm to prepare Na3V2(PO4)3 positive electrode sheet.
[0098] (2) Negative electrode preparation: Using the Na3V2(PO4)3 positive electrode prepared in step (1) as the positive electrode, metallic sodium as the negative electrode, and polymer electrolyte HSPE as the electrolyte, a 2032 button cell was assembled in a glove box, denoted as battery 1. The preparation method of the polymer electrolyte HSPE was the same as in Example 2. Battery 1 was subjected to charge-discharge tests at room temperature, with a test voltage range of 2.5V to 3.8V. The test results are as follows: Figure 5 and Figure 6 As shown.
[0099] Figure 5 and Figure 6 The results show that battery 1 operates at a current density of 100 mAg. -1 The charge-discharge curves for the first and 20th cycles, as well as the changes in specific capacity and coulombic efficiency from the first to the 20th cycles, show that the specific capacity of battery 1 during the first discharge cycle is 116.4 mAh g. -1 The coulombic efficiency is 98.3%, and the specific capacity retention rate after 20 cycles is 98.9%, indicating that the battery has good reversibility and cycle stability.
[0100] Comparative Example 1
[0101] The preparation method of covalent organic frameworks is as follows:
[0102] 0.25 g of 1,4-phenylenediboric acid (BDBA), 10 mL of m-trimethylbenzene (1:1 volume ratio), and 1,4-dioxane solution were subjected to anhydrous and oxygen-free reaction via a double-row tube. The sealed mixture was then transferred to a vacuum oven and reacted at 120 °C for 72 hours. The resulting precipitate was washed three times with anhydrous acetonitrile (treated with molecular sieves), activated with anhydrous acetonitrile (0.15 g of precipitate was immersed in 30 mL of anhydrous acetonitrile) for 24 hours, and then dried in a vacuum oven at 120 °C for 12 hours to obtain the covalent organic framework material COF-1. The obtained COF-1 was sealed and stored in a glove box for later use to prevent hydrolysis.
[0103] from Figure 7 As shown in the SEM images, the covalent organic framework prepared in Comparative Example 1 exhibits irregular sheet-like stacking and severe aggregation.
[0104] Comparative Example 2
[0105] The difference between Comparative Example 2 and Example 2 lies in the reaction temperature used to prepare the covalent organic framework nanotubes. The method for preparing covalent organic framework nanotubes includes the following steps:
[0106] (1) Preparation of electrospun matrix PFM: 1g of polyacrylonitrile (PAN) was dissolved in 5mL of N,N-dimethylformamide (DMF) to prepare a viscous spinning solution. The spinning solution was then transferred into a spinning syringe. The distance between the needle and the receiver was set to 20cm, the receiver rotation speed was set to 100rpm, the injection speed was set to 0.09cm / min, the high voltage was set to 16KV, and the low voltage was set to -2KV. After spinning was completed, the spun membrane was transferred into a vacuum drying oven and vacuum dried at 100℃ for 12h to obtain the electrospun matrix PFM.
[0107] (2) In a glove box atmosphere (Ar, water <0.01ppm, oxygen <0.01ppm), 0.25g of 1,4-phenylenediboric acid (BDBA) and 10mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were prepared into a suspension. 0.05g of the electrospun base film PFM was added to the suspension, and the mixture was sealed in a Schlenk flask. The resulting suspension was then rapidly frozen at 77K (LN2 bath) and evacuated. The mixture was then thawed by ultrasonic treatment. This process was repeated three times to completely remove residual air. The mixture was then reacted at 90℃ for 72h to obtain a covalent organic framework material. This material was washed three times with acetone (previously treated with molecular sieves), activated by immersion in acetone for 24h, and then dried in a vacuum oven at 120℃ for 12h to obtain the covalent organic framework material.
[0108] SEM images of the prepared covalent organic framework materials are shown below. Figure 8 As shown, the results indicate that the covalent organic frameworks prepared at lower temperatures (90℃) exhibit irregular sheet-like structures and cannot present complete hollow nanorod structures.
[0109] Comparative Example 3
[0110] The difference between Comparative Example 3 and Comparative Example 2 is that, when preparing the covalent organic framework material, the mixture was placed at 160°C for 72 hours.
[0111] SEM images of the prepared covalent organic framework materials are shown below. Figure 9 As shown, the results indicate that covalent organic frameworks cannot be synthesized effectively at higher temperatures (120℃), and the synthesized substances exhibit random large particle packing with no obvious distinguishability.
[0112] Comparative Example 4
[0113] The difference between Comparative Example 4 and Comparative Example 2 is that, when preparing the covalent organic framework material, the mixture was placed at 120°C for 12 hours.
[0114] SEM images of the prepared covalent organic framework materials are shown below. Figure 10As shown, the results indicate that covalent organic frameworks cannot be synthesized effectively in a short period of time, and the synthesized substances exhibit irregular sheet-like stacking.
[0115] Comparative Example 5
[0116] The difference between Comparative Example 5 and Comparative Example 2 is that, when preparing the covalent organic framework material, the mixture was placed at 120°C for 100 h.
[0117] SEM images of the prepared covalent organic framework materials are shown below. Figure 11 As shown, the results indicate that, over a longer period of time, the self-assembled hollow tubular covalent organic framework exhibits multiple overlapping morphologies, which cannot meet the requirements for the synthesis of high aspect ratio hollow nanorods.
[0118] Comparative Example 6
[0119] The difference between Comparative Example 6 and Example 2 is that covalent organic framework nanotubes were not added during the preparation of the polymer electrolyte. The preparation method of the polymer electrolyte is as follows:
[0120] (1) Preparation of polymer electrolyte membrane ex-SPE:
[0121] First, 1 g of polyethylene oxide (PEO) and 0.4303 g of sodium salt (NaFTSI) were dissolved in 20 mL of anhydrous acetonitrile to form a transparent homogeneous solution. After stirring for 6 hours, the solution was poured into a mold using a solution casting method. After the acetonitrile evaporated, a film was formed naturally, resulting in a polymer electrolyte membrane ex-SPE, which was then stored in an inert gas atmosphere.
[0122] (2) Preparation of polymer solid electrolyte (SPE):
[0123] In a glove box, the polymer electrolyte membrane ex-SPE prepared in step (1) is placed in a button-type polytetrafluoroethylene mold, and after applying a load of 10N, it is moved into a vacuum drying oven and hot-pressed at 60°C for 12 hours to finally obtain the polymer solid electrolyte SPE.
[0124] The room temperature ionic conductivity of the polymer electrolyte SPE was tested to be 1.22 × 10⁻⁶. -4 S cm -1 The electrochemical window is 5.43 V vs. Na. + / Na, the sodium ion transference number is 0.21.
[0125] Comparative Example 7
[0126] A fully solid-state sodium-ion battery is prepared as follows:
[0127] (1) Preparation of positive electrode sheet: The positive electrode active material powder of sodium vanadium phosphate Na3V2(PO4)3, the conductive agent Super P and the binder PVDF are mixed evenly in a mass ratio of 80:10:10. N-methylpyrrolidone NMP solution is added (the mass ratio of the added amount to the positive electrode active material powder is 2:1). The mixture is ground and stirred into a uniform slurry in a dry environment at room temperature. The slurry is then coated onto a dry and flat aluminum foil, transferred to a vacuum drying oven for drying, and finally cut into round sheets with a diameter of 12 mm to prepare the Na3V2(PO4)3 positive electrode sheet.
[0128] (2) Negative electrode preparation: Using the Na3V2(PO4)3 positive electrode prepared in step (1) as the positive electrode, metallic sodium as the negative electrode, and polymer electrolyte SPE as the electrolyte, a 2032 button cell was assembled in a glove box. The preparation method of the polymer electrolyte SPE was the same as that of Comparative Example 6. The prepared cells were subjected to charge-discharge tests at room temperature, with a test voltage range of 2.5V to 3.8V.
[0129] Tests showed that the battery performed well at a current density of 100 mAg. -1 The initial discharge capacity was only 102.1 mAh g⁻¹, the coulombic efficiency was 93.2%, and the capacity retention after 20 cycles was only 77%.
[0130] The exemplary embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing covalent organic framework nanotubes, characterized in that, The method includes the following steps: (1) Preparation of electrospun base film: Dissolve the polar polymer in a polar organic solvent to prepare an electrospun precursor, and obtain an electrospun base film by electrospun the obtained electrospun precursor. The polar polymer is polyacrylonitrile. (2) Preparation of covalent organic framework nanotubes: Boric acid monomer and electrospun base film are mixed in an organic solvent to form a mixed solution. After freeze degassing, the covalent organic framework is induced to grow in situ through solvothermal reaction and undergo structural rearrangement. The covalent organic framework material is obtained by washing with acetone or acetonitrile. The washed material is activated in acetone for 12 h to 36 h and then vacuum dried to obtain covalent organic framework nanotubes. The boric acid monomer is 1,4-phenylenediboric acid or biphenylenediboric acid. The organic solvent is a mixed solution of m-trimethylbenzene and 1,4-dioxane with a volume ratio of (0.5~1.5):(1.5~0.5). The freeze degassing is performed 1 to 4 times. The temperature of the solvothermal reaction is 100~150 ℃ and the reaction time is 24~96 h. The vacuum drying time is 12~36 h and the vacuum drying temperature is 100~150 ℃.
2. The preparation method according to claim 1, characterized in that, In step (1), the polar organic solvent includes any one of N,N-dimethylformamide, dimethyl sulfoxide, and sulfolane, and the mass-to-volume ratio of the polar polymer to the polar organic solvent is 1~2.75 mg / mL.
3. Covalent organic framework nanotubes prepared by the method according to claim 1 or 2.
4. A polymer-based electrolyte reinforced with covalent organic framework nanotubes, characterized in that, The polymer-based electrolyte comprises the covalent organic framework nanotubes of claim 3, a polymer matrix, and a sodium salt, wherein the polymer matrix comprises polyethylene oxide or polyphenylene ether, and the sodium salt comprises at least one of NaClO4, NaPF6, NaFSI, NaTFSI, and NaBF4.
5. The polymer electrolyte according to claim 4, characterized in that, The mass ratio of the polymer matrix to the sodium salt is 8~20:1; the mass ratio of the covalent organic framework nanotubes to the polymer matrix is 1~10:
100.
6. A method for preparing a polymer-based electrolyte reinforced with covalent organic framework nanotubes according to claim 4 or 5, characterized in that, Includes the following steps: (1) Preparation of polymer electrolyte membrane: Covalent organic framework nanotubes are dispersed in an organic solvent and ultrasonically treated to obtain a covalent organic framework nanotube dispersion. Then, a polymer matrix and sodium salt are added to the covalent organic framework nanotube dispersion to prepare a homogeneous solution. Finally, the solution is cast into a mold to form a membrane, thus obtaining a polymer electrolyte membrane. (2) Vacuum hot pressing and drying treatment: The polymer electrolyte membrane prepared in step (1) is placed in the battery mold and vacuum hot pressing treatment is performed to obtain the polymer electrolyte. The load pressure of the battery mold is 5~20N and the temperature during vacuum hot pressing is 50~80℃.
7. The preparation method according to claim 6, characterized in that, In step (1), the concentration of covalent organic framework nanotubes in the covalent organic framework nanotube dispersion is 1-10%, and the mass fraction of the polymer matrix in the homogeneous solution is 2-10%.
8. The application of the polymer electrolyte according to claim 4 or 5 in an energy storage battery.
Citation Information
Patent Citations
Preparation method of carbon nanotube loaded two-dimensional covalent organic framework electrode material
CN111848892A
Metal organic framework-polymer composite solid electrolyte as well as preparation method and application thereof
CN113937363A